Finland-China Food and Health Science Network - (:unkn) unknown (fi=Turun yliopisto|en=University of Turku|, 2024)
Promotion video for Finland -China Food and Health Network - Growing excellence together The Finland-China Food and Health Network https://fcfh.utu.fi/ is a multidisciplinary network based on the research and educational co-operation between Finnish and Chinese institutions. The network connects 21 Finnish universities and universities of applied sciences and supports higher education-business co-operation. This creats a basis for both new innovations and R&D. The network is linked to the global internationalisation programme which the Ministry of Culture and Education of Finland has launched together with Finnish higher education institutes. The progamme will enable nine pilot networks linked with co-operation in different geographical areas. Read more at: https://heiglobalnetworks.fi/ For more information contact the Finland - China Food and Health sciences network coordination fcfh-coordinator@utu.fi